2012
DOI: 10.1371/journal.pone.0032557
|View full text |Cite
|
Sign up to set email alerts
|

γ-Aminobutyric Acid Transporter 2 Mediates the Hepatic Uptake of Guanidinoacetate, the Creatine Biosynthetic Precursor, in Rats

Abstract: Guanidinoacetic acid (GAA) is the biosynthetic precursor of creatine which is involved in storage and transmission of phosphate-bound energy. Hepatocytes readily convert GAA to creatine, raising the possibility that the active uptake of GAA by hepatocytes is a regulatory factor. The purpose of this study is to investigate and identify the transporter responsible for GAA uptake by hepatocytes. The characteristics of [14C]GAA uptake by hepatocytes were elucidated using the in vivo liver uptake method, freshly is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…EtOH intake had no effect on the kidney GAA synthesis. Recent studies have identified γ‐aminobutyric acid transporter 2 as the transporter responsible for GAA uptake by the hepatocytes (Tachikawa et al., ). There are no reports to date whether EtOH consumption affects this transporter level or activity in the liver and will be the focus of our future studies.…”
Section: Discussionmentioning
confidence: 99%
“…EtOH intake had no effect on the kidney GAA synthesis. Recent studies have identified γ‐aminobutyric acid transporter 2 as the transporter responsible for GAA uptake by the hepatocytes (Tachikawa et al., ). There are no reports to date whether EtOH consumption affects this transporter level or activity in the liver and will be the focus of our future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, rat GAT2 was reported to be involved in the uptake of GAA, γ-butyrobetaine, β-Ala and GABA by hepatocytes, with K m values of 134, 9.3, 35.3, and 22.5 µM, respectively. [62][63][64] Because of the blood concentrations of GAA (3.73 µM), γ-butyrobetaine (0.84-6 µM), β-Ala (<0.5 µM), GABA (0.13 µM) and taurine (130 µM), 22,[65][66][67][68][69] the K m values indicate that GAT2-mediated transport in hepatocytes is not completely saturated under physiological conditions, and the uptake of taurine by rat GAT2 seems to depend on the blood concentration of taurine, revealing the possible endorsement that taurine and its conjugated bile acids are increased by the systemic administration of taurine. 70,71) Immunohistochemistry showed that rat GAT2 is preferentially localized on the sinusoidal membrane of the periportal region (Fig.…”
Section: Hepatic Taurine Uptake Mediated By Gat2mentioning
confidence: 99%
“…При обсуждении сдвигов в содержании пула свободных аминокислот в печени следует учитывать то, что ГАМК и другие изученные аминокислоты могут выполнять в печени функции нутриентов [3,4,8]. Принимая во внимание множественность функций неспецифических ГАМК-Т и ЯПА-ДГ в ткани печени [11,13,14,24], можно предположить, что наблюдаемые метаболические сдвиги являются следствием неспецифической адаптации клеток печени к интенсивной алкогольной нагрузке и периодам её отмены. Следовательно, наблюдаемые изменения при отмене алкоголя и прерывистой алкоголизации могут свидетельствовать о нарушениях утилизации не только ГАМК, но и других её метаболитов, относящихся к нутриентам.…”
Section: заключение и выводыunclassified